Lithium recovery from lithium/magnesium containing waters with biodegradable chitosan based EDTA doped adsorbent - Dagdeviren, Rumeysa; Sevinc, Rumeysa; Unlu, Derya (Separation science and technology, 2025)
The shift from conventional fossil fuel vehicles to electric (and hybrid electric) vehicles plays a crucial role in reducing CO 2 emissions to prevent global warming. Lithium-ion batteries have become a primary choice for electric vehicles due to their high energy density and light weight compared to other battery types. In this study, an adsorbent was developed to adsorb Mg 2+ in solutions containing Li/Mg binary component, thus obtaining lithium in concentrated form. EDTA-chitosan adsorbent based on biodegradable polymer chitosan was synthesized as adsorbent. Adsorbents were characterized using XRD, FTIR, BET and SEM analysis. The effects of adsorbent amount, pH, Li/Mg feed ratio on Mg 2+ removal percentage and separation factor were investigated. The optimum separation conditions are determined as pH = 4.5, adsorbent amount of 0.3 g, Li/Mg feed ratio of 1:20. Under these optimum conditions, 99.36% of magnesium removal percentage and 141.28 of Li/Mg separation factor were obtained.